Seismic Performance Evaluation of Historical Case Study of Armenian Architecture Tekor Church - Şeker, Burçin Şenol; Özkaynak, Merve (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Masonry churches, which are one of the cultural heritages, show the historical background, cultural and religious characteristics of the cities and material properties. Churches in the earthquake zone, which are different from each other in terms of typology and have a special importance, are at risk. The aim of this study is to examine the earthquake behavior of a church sample in Turkey and to provide a guide for structures with similar typology.
Keywords: cultural heritage; damage; FEM model; historical construction; masonry churches; Armenia architecture; Tekor; seismic vulnerability; dziedzictwo kulturowe; szkody; MES; budynek historyczny; architektura Armenii; trzęsienie ziemi